Experiences with and Risks of Internet Use Among Children in Kosovo - Hasan Saliu; Zija Rexhepi; Saranda Shatri; Mimoza Kamberi (University of Maribor Press, 2022)
This paper aims to explore the use of, experiences with, and risks of internet among children in Kosovo. This country has never been involved in the European project called Kids Online. Through a survey based on the Kids Online questionnaire, 437 children aged 11-16 were surveyed in 34 schools across the country. The results show that over 90% of children of this age stay online from one to six hours; YouTube and Instagram are the most preferred platforms; over 90% of them own smartphones. Conversely, many parents have admitted to being less knowledgeable about technology than their children. Parental mediation and schooling remain important, and the paper recommends the introduction of Media Literacy as a separate subject in pre-university education in Kosovo.